The logistics service quality of dry ports: assessment method and development prospects - A. T. Moldabekova; A. Beifert (Экономика: стратегия и практика, 2020)
Sustainable growth of world trade in recent years has significantly influenced development of transportation and global supply chains in terms of multi- and inter-modality as well as intensified the competition between land- and sea-based transport corridors. In the framework of Trans-Eurasian land-based transport corridors, the concept of dry ports has gained a special attention.The aim of this paper is to develop tools for assessing the quality of logistics services of dry ports. An analysis of methodological approaches and models made it possible to underline the following parameters for assessing the quality of logistics services of dry ports: the availability of infrastructure, equipment; the quality of operations and processes in the port; the quality of port management services; price compliance with the level of service quality; the use of information and communication technologies; multimodality and the provision of additional services. Based on an expert survey, weights of each sub-dimension were determined. The data was used in evaluating the “Khorgos Gateways” dry port. According to the results of the study, it was found that the level of quality of the port’s logistics service is average (3.15). Improving the quality of logistics services is required, taking into account new technological solutions that ensure the port’s competitiveness in the transport and logistics market in the context of the development of global supply chains and technological modernization.